Karakteristik Fisikokimia dan Organoleptik Selai Lembar Buah Kesemek Dengan Perbedaan Konsentrasi Pektin - darmawan, Yudha wisnu; quddus, Ati atul; firzriani, Atia (Jurnal Pangan dan Gizi, 2024)
Persimmon fruit is a source of nutrients that are beneficial for the body's health and energy. However, because its use is not optimal, this fruit is susceptible to damage and rot, causing prices to fall and lack of market appeal. However, the pectin content in persimmons is not sufficient for making sheet jam, so it is necessary to add pectin. This research aimed to evaluate the effect of different pectin concentrations on the chemical and organoleptic characteristics of persimmon jam, as well as determine the best pectin concentration. This research used a Completely Randomized Design (CRD) method with four single treatments, namely the addition of pectin with a concentration of T0 (0%), the concentration of T0 (0%), T1 (0.5%), T2 (1.0%), T3 (1.5%). The results showed that the addition of different concentrations of pectin significantly influenced the value of vitamin C, water content, antioxidants, total soluble solids, as well as organoleptic attributes of texture and overall persimmon sheet jam. However, there was no significant effect on the organoleptic attributes of taste, aroma and colour. The best pectin concentration for persimmon sheet jam is the T3 treatment (1.5% pectin), which has the following characteristics: water content 36.13%, Vitamin C 3.10 mg/100 grams, antioxidant activity (IC50) 93 .70 ppm, total dissolved solids 66.1˚Brix, and organoleptic assessments for taste, aroma, colour, texture and overall attributes were 2.52, 2.24, 2.60, 2.88 and respectively.